Critical Synthesis Package: Mini-Clinical Evaluation Exercise (mCEX) - Linda Perkowski (Association of American Medical Colleges, 2014)
Abstract This Critical Synthesis Package contains: (1) a Critical Analysis of the psychometric properties and application to health science education of the Mini-Clinical Evaluation Exercise (mCEX), and (2) a copy of the mCEX and scoring instructions developed by John Norcini, PhD for the American Board of Internal Medicine. The mCEX is a workplace-based educational tool designed to directly assess clinical skills of residents during training. It utilizes an observation-based 9-point Likert-type scale assessing six domains: Interviewing, Physical Examination, Humanistic Qualities/Professionalism, Clinical Judgment, Counseling and Organization/Efficiency, and Overall Clinical Competence. Scoring options are unsatisfactory (1-3), marginal (4), satisfactory (5-6), superior (7-9), and not applicable. A total score is calculated by determining the mean of the six domain ratings. This instrument was developed for use as a formative assessment tool with internal medicine residents but has been used with other specialties and with undergraduate medical students. The instrument has been demonstrated to be both feasible and reliable if used as designed, and multiple observations of the trainee are provided. Limitations in the reliability of the mCEX exist when assessor training is marginal, when scores are used to distinguish among domains, and/or when the mCEX is employed as a high stakes assessment. The mCEX has been used in a variety of clinical settings and in both graduate and undergraduate medical training programs and has demonstrated positive correlations with other instruments of proven validity. Additional studies are needed to address the mCEX's use in trainees with specialties other than internal medicine, to further investigate the impact of rater selection and training on the reliability of the scores, and to further document evidence of the measure's educational effects.